The Impact of Ownership, Conflict, and Asymmetry on Accounting Conservatism in IDX 2020-2022 - Riyanto, Cantika Zalfa Alifiana; Muslimin (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study identifies factors that influence accounting conservatism in oil, gas, & coal sub-sector companies on the Indonesia Stock Exchange in 2020-2022. The independent variables studied include ownership structure, conflict of interest, and information asymmetry. Using quantitative methods and fixed effects model panel data regression techniques, this study analyzed data from 21 companies selected through purposive sampling. The results showed that ownership structure has a positive and significant effect on accounting conservatism, where greater institutional ownership encourages the presentation of conservative financial statements. However, conflict of interest and information asymmetry have no influence on accounting conservatism because the majority of companies do not distribute dividends and adopt the fair value principle in IFRS which reduces information asymmetry between shareholders and management.